A new queuing strategy for large scale ATM switches. - Guizani, M. (IEEE Communications magazine)
In this article, different buffering techniques used to solve the contention problem in ATM switching architectures are compared. Then, the buffer requirements needed to achieve a given quality of service (QoS) is determined. Based on the results, we propose a combined central and output queuing (CCOQ) technique to be used in designing large-scale ATM switches for high-speed networks